2013
DOI: 10.1016/j.breast.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of catechol estrogens metabolism pathway genes and breast cancer risk in Mexican women

Abstract: Breast cancer is associated to estrogen exposure. Allelic variants involved in estrogen metabolism might change the risk of developing this neoplasia. We examined the potential association of breast cancer risk in Mexican women with the polymorphisms CYP1A1 rs1048943, CYP1B1 rs1056836, COMT rs4680, GSTP1 rs1695, GSTT1 null and GSTM1 null which are involved in estrogen metabolism pathway. This study included 150 cases and 150 controls. A significant association was observed between, CYP1A1 rs1048943 (OR = 1.95,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 66 publications
3
16
1
Order By: Relevance
“…In the only previous related study carried out in Mexico, GSTP1 polymorphisms were associated with an increased breast cancer risk; no association was observed for GSTM1 and GSTT1 (Martínez-Ramírez et al, 2013). The differences between this study and our results are likely related to ethnicity and methodological factors.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In the only previous related study carried out in Mexico, GSTP1 polymorphisms were associated with an increased breast cancer risk; no association was observed for GSTM1 and GSTT1 (Martínez-Ramírez et al, 2013). The differences between this study and our results are likely related to ethnicity and methodological factors.…”
Section: Discussioncontrasting
confidence: 56%
“…In Mexico, only one related study has been carried out, in which subjects in the country's central zone were analyzed (Martínez-Ramírez et al, 2013). Thus, the purpose of this study was to investigate the genotypic and allelic frequencies of polymorphisms in GSTM1, GSTT1, GSTP1, and GSTM3 to determine whether an association exists between polymorphisms in these genes and the risk of breast cancer in subjects from northeastern Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we observed similar null GSTM1 genotype frequencies in our control group at those that had been previously reported in Mexico (Pérez-Morales et al, 2011;Martínez-Ramírez et al, 2013;Sandoval-Carrillo et al, 2014). The genotypic GSTM1 null frequencies were 38 and 45% in the control group and in patients with BC, respectively, suggesting an association of this allele as a risk factor in BC.…”
Section: Discussionsupporting
confidence: 91%
“…The single nucleotide polymorphism (SNP) G>A (rs4680) leads to an amino acid change of Val to Met in the position 108/158 in cytoplasmic/ membranous enzyme form, Submit your Manuscript | www.austinpublishinggroup.com respectively, and is generally known as Val158Met. This SNP has important (two-to fivefold) impact on the enzymatic activity as those individuals homozygous for the Val (GG) have high activity enzyme variant, those with Met/Met (AA) possess low activity protein and heterozygous genotype carriers (Val/Met, GA) have the enzyme form with intermediate activity [7,12,14,17,[19][20][21][22][23][24][25][26][27][28]. It means that alteration in the respective genotype leads to the change in efficacy of O-methylation of different endogenous and exogenous catecholic compounds (including for example catechol estrogens, but also flavonoids like quercetin, fisetin and different flavanols) and therefore also to the increased amounts of circulating catechols with significantly different bioactivities compared to their O-methylated metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that this genetic change may have some role in the pathogenesis (initiation and/or progression) of CLL. It is well known that hydroxylated intermediates of estradiol (2-and 4-hydroxylated estradiols) can be oxidated to highly reactive semiquinones and quinones which may induce DNA damage and cause therefore cancer development [15][16][17][18][19][20][21]25,[29][30][31][32]. These harmful effects are contravened by detoxification enzymes, mainly by COMT that catalyzes O-methylation of different catechols and facilitates their excretion from the body [14,20].…”
Section: Discussionmentioning
confidence: 99%